Legionella pneumophila Serogroup 1 in the Water Facilities of a Tertiary Healthcare Center, India - Rama Chaudhry; K. Sreenath; Valavane Arvind; E.V. Vinayaraj; Sagar Tanu (Emerging Infectious Diseases, 2017)
Proactive environmental surveillance for Legionella pneumophila in hospitals that treat immunocompromised patients is a useful strategy for preventing nosocomial Legionnaires’ disease. We report the presence of L. pneumophila serogroup 1 in 15.2% of the water systems of our tertiary healthcare center, which should prompt health officials to formulate mitigation policies.